Concepts in Rehabilitation of Burn Patients - Rahman, Md Shahidur; Shakoor, MA (Journal of Bangladesh College of Physicians and Surgeons, 2007)
Burn is not the skin loss only. Functional and psychological outcome must be assessed and treated accordingly. Prevalence of burn injury is very high in Bangladesh though exact statistics is not available. Houses of poor people especially in the slum area, which are made of combustible materials, are vulnerable to set off fire. Chemical burns like throwing acids by culprits are common in our country. Hospitals are treating these patients without proper medical and psychological rehabilitation. This article will review the rehabilitation concepts of burn injury and provide some information to those physicians and surgeons who treat burn injury. (J Bangladesh Coll Phys Surg 2007; 25 : 139-143)